UJI KUAT TEKAN, DAYA SERAP AIR DAN DENSITAS MATERIAL BATU BATA DENGAN PENAMBAHAN AGREGAT LIMBAH BOTOL KACA - Ardi, Andi Wahyuni; Iswadi, Iswadi; Said L, Muh (JFT: Jurnal Fisika dan Terapannya, 2016)
This experiment aims to know the influence of the increment of glass bottle waste to the pressure power, the water absorptive power and the density of the brick material and to know the comparison of the increment of glass bottle waste composition value to the brick material which produces the pressure power, absorptive power and the density match with standard value. This experiment uses tool test like beam with a size long 11 cm, wide 11 cm, height 5 cm with some various of the aggregate of glass bottle composition 0 %, 10 %, 20 %, 30 %, and 40 %. Making brick with the combination of soil, sand, water and the combination of aggregate of blass bottle waste, in the drying process within 1-2 days then burning in the oven with temperature 900 oC for 3,5 hours. And then the brick is tested 3 parameters are the pressure, the absorptive and the density. Based on the test result it was gotten each of the parametre tests are the minimum value of the pressure is 223,41 kg/cm2 and the maximum is 253,37 kg/cm2 (based ont the class category 200 to 250 based on SII-0021-1978); the water absorptive value was gotten in minimum is 9,38 % and the maximum is 19,05 % (based on standard SII 15–2094–2000) and the dencity value is 1,48 - 1,64 gr/cm3 (based on standard).